The Stress Kinase JNK Regulates Gap Junction Cx43 Gene Expression and Promotes Atrial Fibrillation in the Aged Heart - Yan, Jiajie (J Mol Cell Cardiol, 2017)
BACKGROUND: The stress kinase c-jun N-terminal kinase (JNK) is critical in the pathogenesis of cardiac diseases associated with an increased incidence of atrial fibrillation (AF), the most common arrhythmia in the elderly. We recently discovered that JNK activation is linked to the loss of gap junction connexin43 (Cx43) and enhanced atrial arrhythmogenicity. However, direct evidence for JNK-mediated impairment of intercellular coupling (cell-cell communication) in the intact aged atrium is lacking, as is evidence for whether and how JNK suppresses Cx43 in the aged human atrium. METHODS AND RESULTS: JNK activity in human atrial samples is correlated with both reduced Cx43 expression and increasing age. Using a unique technique of optical mapping space constant measurement, we found that impaired intercellular coupling and reduced Cx43 were linked to enhanced activation of JNK in intact aged rabbit atria. These JNK-associated alterations were further confirmed in naturally JNK activated aged mice and in cardiac-specific inducible MKK7D (JNK upstream activator) young mice. Moreover, JNK inhibition, using either JNK specific inhibitors in aged wild-type (WT) mice and JNK activator anisomycin-treated young WT mice or JNK1/2 dominant-negative mice with genetically inhibited cardiac JNK activity, completely eliminated these functional abnormalities. Furthermore, we discovered for the first time that long-term JNK activation downregulates Cx43 expression via c-jun suppressed transcriptional activity of the Cx43 gene promoter. CONCLUSION: Our results demonstrate that JNK is a critical regulator of Cx43 expression, and that augmented JNK activation in aged atria downregulates Cx43 to impair cell-cell communication and promote the development of AF. JNK inhibition may represent a promising therapeutic approach to prevent or treat AF in the elderly.